A new species of Platychasma (Lepidoptera: Notodontidae) from China - Chen, Liusheng; Kishida, Yasunori; Wang, Min (Zootaxa, 2008)
The notodontid genus Platychasma was established by Butler in 1881, and hitherto comprised only two species: Platychasma virgo Butler, 1881 and P. flavida Wu & Fang, 2003. The former is distributed in China, Japan and Korea (Sugi 1982; Park et al. 1999; Wu & Fang 2003a, b), while the latter is found only in China (Wu & Fang 2003a, b). During moth surveys in southern and central China, the authors collected several specimens with typical external features of the subfamily Platychasmatinae (antenna filiform, quadrifid forewing venation and forewing dorsum bidentate). However, the specimens collected differed from both P. virgo and P. flavida in several morphological features, notably the forewing shape and male genitalia. Following comparison with P. virgo from Japan and with the original description and illustrations of P. flavida, these Chinese specimens are hereby described as new, as follows: